Efforts Of The Madrasah Head In Enhancing Teacher Professionalism At Madrasah Diniyah Al-Muttaqiin - Rosyidah, Binti; Hidayati, Denok Trisni; Jumari, Jumari; Gani, Saifuddin A.; Amin, Nurul (STAI Miftahul Ula Nganjuk, 2024)
The importance of teacher professionalism in teaching serves as a benchmark for the Madrasah Head, who plays a crucial role in enhancing teacher professionalism. This study aims to assess the level of teacher professionalism in teaching at Madrasah Diniyah Al-Muttaqiin, describe the efforts made by the Madrasah Head in improving teacher professionalism at Madrasah Diniyah Al-Muttaqiin, and identify the factors that hinder and support the Madrasah Head's efforts in enhancing teacher professionalism at Madrasah Diniyah Al-Muttaqiin. This qualitative research adopts a descriptive approach. The main subjects of this study are the Head of Madrasah Diniyah Al-Muttaqiin, with teachers and staff as informants. Data collection was conducted through observation, interviews, and documentation. Data validity was ensured through source triangulation. The data analysis technique used is interactive analysis, which includes data reduction, data presentation, and verification. A professional teacher is defined as one who possesses pedagogical, professional, social, and personal competencies. The findings of this study are as follows: Teacher professionalism in teaching at Madrasah Diniyah Al-Muttaqiin has improved due to the support of the Madrasah Head. The Madrasah Head conducts supervision and evaluation, discipline training, motivation, and recognition for teachers. Supporting factors for improving teacher morale include the Madrasah Head's attention to the material and spiritual needs of teachers. The inhibiting factors include the lack of teacher awareness regarding the importance of discipline in fulfilling teaching duties, both individually and collectively, at the Madrasah.